Death Penalty and Psychiatric Evaluation in Japan - Kashiwagi, Hiroko; Hirabayashi, Naotsugu (Frontiers in Psychiatry, 2018)
Japan recently ordered a string of death sentences for offenders with mental illness. Based on the verdicts, we describe cases where one or more psychiatrists conducted psychiatric evaluations for several months and testified in lay judge courts. We compared these cases with those in which the death penalty was avoided, or the mandating treatment order was applied. Additionally, we discuss a trend towards more severe punishment and Japanese cultural background seen in a public opinion survey. Moreover, we introduce a research report that concluded a strong correlation between the number of victims and death penalty verdict. In Japan, lay judge trials determine the sentencing of the defendant and the verdict of guilty or not guilty, and it can be difficult for psychiatrists to help lay judges understand psychiatric symptoms and the relationship between symptoms and criminal responsibility through their testimony. We believe the right to life is the most fundamental of human rights and that the death penalty is inhumane. The death penalty also eliminates the possibility of treatment or rehabilitation, despite the fact that psychiatrists should support the possibility of treatment or rehabilitation in all cases. Further, the Japanese Penal Code does not permit execution for those mentally ill deemed unable to receive sentence; however, it is unclear who will conduct these evaluations and how they will do so. We describe our beliefs of how psychiatrists should act in these situations.